OPERA AND FILM – AN UNLIKELY MARRIAGE - Julianna KÖPECZI (Studia Universitatis Babeş-Bolyai. Musica)
The aim of the following study is to analyze the manner in which opera music influenced film and became a crucial building block of certain cinematic narratives, in such films as Jonathan Demme’s Philadephia (USA, 1993), Luc Besson’s The Fifth Element (France, 1997) and Liliana Cavani’s Il portiere di note / The Night Porter (Italy, 1974). By revealing the correspondence between these audiovisual mediums and examining the common language used by them we intent to reveal numerous facets of this symbiotic relationship, all put in the service of lending meaning to the film, thus making the viewer’s escapist adventure truly unique.